Mesoporous hollow MnCuAl layered triple hydroxides nanocomposite synthesized via microwave assisted technique for symmetrical supercapacitor. (19th October 2017) - Chandrasekaran, Nivedhini Iswarya; Manickam, Matheswaran
Abstract: Hollow MnCuAl layered triple hydroxides nanocomposite synthesized using microwave assisted technique possess an immense potential as a high performance electrode material for forthcoming generation energy storage warehouse. The layered triple hydroxide nanocomposite structure possesses a furry morphology with mesoporous nature. The electrochemical performance evinces the idiosyncratic architecture with highly mesoporous nature plays a prominent character in achieving high capacitance with superior life cycle stability. This structure not only supports for adequate reaction sites and also speed up electrolyte ions to reach the reacting sites. The MnCuAl layered triple hydroxide retains 93.46% of initial capacitance after 5000 cycles and having an equivalent series resistance of 0.701 Ω. Prominently, the assembled symmetric solid state supercapacitor device using MnCuAl layered triple hydroxide delivers a high energy density (101.75 W h kg −1 ) at a power density of (900 W kg −1 ). The results show the symmetric supercapacitor made from MnCuAl layered triple hydroxide nanocomposite to be a propitious candidate for energy storage applications. Graphical abstract: Highlights: An approach to acquire a porous hollow MnCuAl layered triple hydroxide is presented. Wide potential window of 0–1.8 V is achieved. Symmetric supercapacitor with good specific capacitance and long cycling stability. High energy and power density have been obtained.